TELAAH KRITIS TERHADAP KAIDAH USHULIYAH LUGHAWIYAH - Muhamad Ikhwan; Kasiyono Kasiyono (STIT Sunan Giri Bima, 2021)
The science of Ushul Fiqh is one of the many disciplines that must be mastered by everyone who wants to formulate a law. The academic argument about the importance of ushul fiqh is a fact which shows that not all legal events that arise can be found definitively in the Qur’an or the Prophet's hadith. This view is supported by the analysis of the Imam Shafi'i, that according to him there are four patterns of mentioning the instructions of the Qur’an, first, an explicit explanation of the obligations that must be carried out by his creatures; second, the affirmation of some obligations while the procedures for their implementation are explained through the sunnah of the prophet; third, the determination of the hadith of the apostle for things that are not definitively regulated in the Qur’an; fourth, obligations that must be sought through the ijtihad mechanism. Included in the realm of ushul fiqih study is linguistic analysis (ushuliyah-lughawiyah) of a lafadz concerning the clarity and obscurity of a lafadz and its implications for its content. The clear category of lafadz (wudhuh) includes dzahir, nash, mufassar and muhkam while the unclear lafadz category (ghairu wudian al-dilalah) includes khafi, musykil, mujmal and mutysabih.